2021
DOI: 10.1186/s12957-021-02137-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a miRNA-related expression signature for tumor mutational burden in colorectal cancer

Abstract: Background Tumor mutational burden (TMB) is a promising predictor, which could stratify colorectal cancer (CRC) patients based on the response to immune checkpoint inhibitors (ICIs). MicroRNAs (miRNAs) act as the key regulators of anti-cancer immune response. However, the relationship between TMB and miRNA expression profiles is not elucidated in CRC. Methods Differentially expressed miRNAs (DE miRNAs) between the TMBhigh group and the TMBlow group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…There are also many reports about miRNAs in CRC. Xu et al reported the relationship between miRNA expression and tumour mutation burden in CRC [ 10 ]. miR-4319 can inhibit the proliferation, migration and invasion of CRC cells and inhibit the cell cycle, acting as a tumour suppressor gene in CRC by targeting ABTB1 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are also many reports about miRNAs in CRC. Xu et al reported the relationship between miRNA expression and tumour mutation burden in CRC [ 10 ]. miR-4319 can inhibit the proliferation, migration and invasion of CRC cells and inhibit the cell cycle, acting as a tumour suppressor gene in CRC by targeting ABTB1 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of miRNAs plays an important role in various cancer development and progression, including breast cancer [ 32 , 33 ]. Aberrant expression of miR-381-3p is observed in many types of cancers, suggesting that miR-381-3p might play a crucial role in tumorigenesis and progression [ 13 , 18 , 34 – 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that previous studies have identified multiple lncRNAs and miRNAs with critical functions in EC and other cancers [20][21][22][23][24][25][26]. Future studies should focus on the clinical applications of these lncRNAs and miRNAs.…”
Section: Discussionmentioning
confidence: 99%